2014
DOI: 10.3109/13880209.2013.879906
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of caffeic acid in rats and its absorption properties in the Caco-2 cell model

Abstract: CA was shown to have low oral bioavailability in rats, low intestinal absorption, and poor permeability across Caco-2 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 13 publications
3
31
0
1
Order By: Relevance
“…Many biological activity are attributed to esters derivatives of caffeic acids, such as anti‐inflammatory activity, anti‐cancer by induction of apoptosis, antimicrobial, immunomodulatory, as described in the introductory part of this manuscript. Furthermore, it has been shown previously that caffeic is absorbed in rats and has an absolute bioavailability in humans around 95% . To the best of our knowledge, there are no data available about caffeic acid ethyl ester bioavailability, but a publication showed that caffeic acid phenetyl ester was resorbed in rats .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many biological activity are attributed to esters derivatives of caffeic acids, such as anti‐inflammatory activity, anti‐cancer by induction of apoptosis, antimicrobial, immunomodulatory, as described in the introductory part of this manuscript. Furthermore, it has been shown previously that caffeic is absorbed in rats and has an absolute bioavailability in humans around 95% . To the best of our knowledge, there are no data available about caffeic acid ethyl ester bioavailability, but a publication showed that caffeic acid phenetyl ester was resorbed in rats .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown previously that caffeic is absorbed in rats and has an absolute bioavailability in humans around 95%. [22,23] To the best of our knowledge, there are no data available about caffeic acid ethyl ester bioavailability, but a publication showed that caffeic acid phenetyl ester was resorbed in rats. [24] Caffeic acid and derivatives could then explain, at least in part, the oral antimalarial activity of traditional medicinal plants where these compounds are abundant.…”
Section: Discussionmentioning
confidence: 99%
“…Herbal complicated compounds are difficult to be detected due to lower concentration and interference from endogenous compounds in vivo, however, compared to in vivo pharmacokintic study, the experimental conditions of the in situ vascularly perfused rat intestine preparation, such as drug concentration, perfusate flow and the composition of perfusate, can be properly adjusted to survey the effect on the intestinal absorption of the tested drugs [14,18], it is an ideal approach for traditional Chinese medicines (TCM) to investigate the target constituents and enhance their detected concentration. Besides, the in situ vascularly perfused rat intestine preparation is advantageous of that the circulation and morphology of the tissues remain intact, which is precise assessment of the contribution of intestinal absorption of drug [14], and we had successfully investigated intestinal absorption properties of caffeic acid using this method [19]. In this study, we used this method to investigate intestinal absorption of these thirteen flavonoids of XBXT-2 and the in situ experiment date analysis for the intestinal absorption was calculated as follows: Intestinal absorption% = content in perfused/content in 0.2 g XBXT-2 × 100%.…”
Section: Quantification and Absorptionmentioning
confidence: 99%
“…Both in vivo and in vitro studies must be done for accurate determination of engagement and bioavailability of these phenolic acids. It has already been performed for caffeic acid and p-coumaric acid [30,65,66].…”
Section: Wheat Antioxidants In Breakfast Foodsmentioning
confidence: 99%
“…These compounds are present as bound forms, respectively, as phenolic acids (85%) in maize, wheat and maize (75%), and rice (62%). Cinnamic acids have been categorized as bioactive ingredients of the diet because they are bound to structural compounds of the cell wall [30,31]. The schematic representation of wheat grain fractions is shown in Figure 1.…”
Section: Phenolic Compounds Present In Wheatmentioning
confidence: 99%